Exposure to Ketamine Anesthesia Affects Rat Impulsive Behavior - Melo, António; Leite-Almeida, Hugo; Ferreira, Clara; Sousa, Nuno; Pêgo, José M. (Frontiers in Behavioral Neuroscience, 2016)
Introduction: Ketamine is a General Anesthetic that activates several neurotransmitter pathways in various part of the brain. The acute effects as general anesthetic are the most well-known and sought-after: to induce loss of responsiveness and to produce immobility during invasive procedures. However, there is a concern that repeated exposure might induce behavioral changes that could outlast their acute effect. Most research in this field describes how GA affects cognition and memory. Our work is to access if general anesthesia with ketamine can disrupt the motivational behaviour trait, more specifically measuring impulsive behaviour. Methods: With the aim to evaluate the effects of exposure to repeat anesthetic procedures with ketamine in motivational behavior, we tested animals in a paradigm of impulsive behavior, the Variable Delay-to-Signal (VDS). In addition, accumbal and striatal medium spiny neurons morphology was assessed. Results: Our results demonstrated that previous exposure to ketamine deep-anesthesia affects inhibitory control (impulsive behavior). Specifically, ketamine exposed animals maintain a subnormal impulsive rate in the initial periods of the delays. However, and in longer delays while control animals progressively refrain their premature unrewarded actions, ketamine-exposed animals show a different profile of response with higher premature unrewarded actions in the last seconds. Animals exposed to multiple ketamine anesthesia also failed to show an increase in premature unrewarded actions between the initial and final periods of 3s delays. These behavioral alterations are paralleled by an increase in dendritic length of medium spiny neurons of the nucleus accumbens. Conclusions: This demonstrates that ketamine anesthesia acutely affects impulsive behavior. Interestingly, it also opens up the prospect of using ketamine as an agent with the ability to modulate impulsivity trait.